Drugs and natural products for the treatment of COVID-19 during 2020, the first year of the pandemic - Elia G. Jaimes-Castelán; Claudia González-Espinosa; Gil A. Magos-Guerrero; Isabel Arrieta-Cruz; Manuel Jiménez-Estrada; Ricardo Reyes-Chilpa; Jorge I. Castillo-Arellano (Permanyer, 2024)
This work aimed to show which treatments showed efficacy against coronavirus disease 2019 (COVID-19); therefore, the results of 37 clinical trials started in 2020 and completed in 2021 are reviewed and discussed here. These were selected from databases, excluding vaccines, computational studies, in silico, in vitro, and those with hyperimmune sera from recovered patients. We found 34 drugs, one vitamin, and one herbal remedy with pharmacological activity against symptomatic COVID-19. They reduced mortality, disease progression, or recovery time. For each treatment, the identifier and type of trial, the severity of the disease, the sponsor, the country where the trial was conducted, and the trial results are presented. The drugs were classified according to their mechanism of action. Several drugs that reduced mortality also reduced inflammation in the most severe cases. These include some that are not considered anti-inflammatory, such as Aviptadil, pyridostigmine bromide, anakinra, imatinib, baricitinib, and bevacizumab, as well as the combination of ivermectin, aspirin, dexamethasone, and enoxaparin. Nigella sativa seeds with honey have also been reported to have therapeutic activity. On the other hand, tofacitinib, novaferon with ritonavir, and lopinavir were also effective, as well as in combination with antiviral therapies such as danoprevir with ritonavir. The natural products colchicine and Vitamin D3 were only effective in patients with mild-to-moderate COVID-19, as was hydroxychloroquine. Drug repositioning has been the main tool in the search for effective therapies by expanding the pharmacological options available to patients.